2015
DOI: 10.1039/c5nr02099a
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of porous array films on a filament induced micro-gap electrode pair and their use as resistance-type gas sensors with enhanced performances

Abstract: Resistance-type metal-oxide semiconductor gas sensors with high sensitivity and low detection limit have been explored for practical applications. They require both sensing films with high sensitivity to target gases and an appropriate structure of the electrode-equipped substrate to support the sensing films, which is still challenging. In this paper, a new gas sensor of metal-oxide porous array films on a micro-gap electrode pair is designed and implemented by taking ZnO as a model material. First, a micro-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Both sensors demonstrate fast response when exposed to high concentration (above 20 ppm). Besides, it can be deduced from the results shown in Figure c that the response behavior of the sensor using N–C@α-Fe 2 O 3 NOs (3 nm) can be correlated to the vapor concentration of TEA following the conductance model commonly applied to MOS chemiresistive sensors, S = a [C] b + 1, , where S is the sensor response value and C is the vapor concentration of TEA. The equation can be rearranged in a logarithm format showing the linear relationship as log­( S – 1) = b log­( C ) + log­( a ) at certain operating temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Both sensors demonstrate fast response when exposed to high concentration (above 20 ppm). Besides, it can be deduced from the results shown in Figure c that the response behavior of the sensor using N–C@α-Fe 2 O 3 NOs (3 nm) can be correlated to the vapor concentration of TEA following the conductance model commonly applied to MOS chemiresistive sensors, S = a [C] b + 1, , where S is the sensor response value and C is the vapor concentration of TEA. The equation can be rearranged in a logarithm format showing the linear relationship as log­( S – 1) = b log­( C ) + log­( a ) at certain operating temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al succeeded with the same method of free-standing microchip and microheater (Figure j). Further representative works relevant to this sensing strategy are summarized in Table . …”
Section: Chemical Sensors Integrated With Nature-inspired Structuresmentioning
confidence: 99%
“…For instance, Xu et al demonstrated that a 2DOM ZnO sensor can retain the long-term sensing stability for 16 months. 85 Currently, a diversity of metal oxide 2DOM lms have been in situ constructed on desired sensor substrates to fabricate SMO gas sensors via sputtering and solution-related templating methods. 48,54,86 For instance, Xu et al recently reported a new photochemistry-based solution-dipping method to prepare monolayer macroporous SnO 2 arrays with controlled surface pore sizes (varying the UV irradiation time) on ceramic tubes for ethanol sensors, showing rapid response-recovery rate (within 10 s) and high stability for temperatures lower than 300 C. 87 However, the use of wide-spaced electrodes (in millimeters) on ceramic tubes can engender ultrahigh resistance (usually in hundreds of megaohms) in the metal oxide sensing lm, which hampers the convenient measurement of sensor resistance using conventional electric circuits.…”
Section: D Macroporous Arrays For Gas Sensingmentioning
confidence: 99%